Zastosowanie wykładnika Hursta w analizie sprzedaży towarów w przedsiębiorstwie - Skoczylas, Krystyna (Hurst Exponent Application During the Analysis of Sale in an Enterprise, 2006)
The paper presents the algorithm and interpretation of Hurst exponent. It has been used during the analysis of sales in selected enterprise. The Hurst exponent was calculated empirically and theoretically, then the data was compared to verify if the analyzed time series have long memory. Real time series representing day's, week's and month's totality sale were subjected to the analysis. Cycle of sale was detected by the Hurst exponent.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (17); 2006; nr 1123, s. 242-255